Stochastic modelling of textile structures for resin flow analysis - Gommer, Frank (2013)
This work addresses the characterisation of the micro-structure of fibre bundles in reinforcement textiles for composites and its influence on resin flow in liquid composite moulding (LCM) processes. Random variations in local filament spacing result in a non-uniform flow velocity field. Merging flow fronts due to differences in local flow velocities can lead to gas entrapment in the matrix phase. This results in formation of micro-scale defects, which can significantly reduce the matrix-dominated mechanical properties of the finished composite.